Conductive Nanocomposites: Positive Temperature Coefficient (PTC) Evolution of Segregated Structural Conductive Polypropylene Nanocomposites with Visually Traceable Carbon Black Conductive Network (Adv. Mater. Interfaces 17/2017). Issue 17 (8th September 2017) - Zhao, Shuaiguo; Li, Guojie; Liu, Hu; Dai, Kun; Zheng, Guoqiang; Yan, Xingru; Liu, Chuntai; Chen, Jingbo; Shen, Changyu; Guo, Zhanhu
Abstract : Polypropylene conductive composites with carbon black selectively distributed at the interfaces between polypropylene matrixes are described by Kun Dai, Zhanhu Guo, and co‐workers in article number1700265 . This segregated conductive network is damaged and constructed by thermal diffusion and aggregation of carbon black, leading to an increasing and then decreasing positive temperature coefficient (PTC) effect.